2022
DOI: 10.3389/fpls.2021.771992
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, Biochemical, and Root Proteome Networks Revealed New Insights Into Salt Tolerance Mechanisms in Pongamia pinnata (L.) Pierre

Abstract: Cultivation of potential biofuel tree species such as Pongamia pinnata would rehabilitate saline marginal lands toward economic gains. We carried out a physiological, biochemical, and proteomic analysis to identify key regulatory responses which are associated with salt tolerance mechanisms at the shoot and root levels. Pongamia seedlings were grown at 300 and 500 mM NaCl (∼3% NaCl; sea saline equivalent) concentrations for 15 and 30 days, gas exchange measurements including leaf net photosynthetic rate (Asat)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Since chalcone synthase is the first enzyme in the flavonoid biosynthetic pathway, its expression and regulation are important [57]. The significant enrichment of CHS protein in Pongamia roots under salt treatment contributes to the protection of Pongamia with high antioxidant activity from ROS damage and promotes root growth under high salt stress [58]. The results of this study showed that the abundance of CHS2 was significantly increased after the 500 mM NaCl treatment, indicating that R. soongorica could be used to increase secondary metabolites to mitigate salt damage by up-regulating the expression of CHS2.…”
Section: Discussionmentioning
confidence: 99%
“…Since chalcone synthase is the first enzyme in the flavonoid biosynthetic pathway, its expression and regulation are important [57]. The significant enrichment of CHS protein in Pongamia roots under salt treatment contributes to the protection of Pongamia with high antioxidant activity from ROS damage and promotes root growth under high salt stress [58]. The results of this study showed that the abundance of CHS2 was significantly increased after the 500 mM NaCl treatment, indicating that R. soongorica could be used to increase secondary metabolites to mitigate salt damage by up-regulating the expression of CHS2.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, leaves act as a bridge in the response to salt stress. Salt stress leads to a Na + and Climbalance, which damages photosystem II (PS II) in the chloroplast, resulting in an increased proportion of absorbed light energy being dissipated as heat and uorescence (Marriboina et al 2022). Na + slows the photosynthetic rate by disrupting proton dynamics, chloroplast function, and carbon xation enzyme activity (Van Zelm et al 2020).…”
Section: Introductionmentioning
confidence: 99%